Australian politics in the global era - Capling, Ann, 1959-; Considine, Mark, 1953-; Crozier, Michael, 1956- (Melbourne : Addison Wesley Longman, 1998)
Designed to provide a brief introduction to the effects of globalisation on Australian politics, this book is divided into sections on political economy, political institutions, and political culture.
Includes index.
Bibliography
Keywords: International economic relations; Australia -- Economic policy; Australia -- Economic conditions; Australia -- Politics and government